Empirische Analyse des Offenlegungszeitpunkts von Jahresabschlüssen nach dem EHUG; Timing of Disclosure for Financial Statements in Germany after the 2007 EHUG Act - Klaus Henselmann; Devrimi Kaya (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Rechnungswesen und Prüfungswesen, 2008)
Timing of Disclosure for Financial Statements in Germany after the 2007 EHUG Act: The paper analyses the timing of disclosing financial statements for small and medium enterprises (SME) in Germany in 2007 and 2008. Comparisons of different regional areas and different company sizes are made and possible explanations for the results discussed.
Keywords: G18; G38; K22; M41; M42; 650; Rechnungslegungspolitik; Publizität; Größenklassen; Klein- und Mittelbetrieb (KMU); Elektronisches Unternehmensregister; Financial Reporting; Accounting Policy; Disclosure; Commercial Register; SME